Urban design in a historic context: Evaluation of the renovation project of Sahibabad Meydan in Tabriz - Soleimani, Meysam (Yildiz Technical Univ, Fac Architecture, 2022)
The present study aims to evaluate the renovation of Sahibabad Meydan which is part of a large-scale urban project designed to reorganise the traditional commercial axis of Tabriz. The project has been stalled for more than a decade as the implemented first phase encountered a serious financial failure. The renovation of historic sites has become an important task in Iranian cities that experienced a dramatic urban change over the past century. The present study highlights the importance of Urban Morphology in designing historic contexts in contemporary Iranian cities. The urban transformation of Tabriz is analysed at the city level to understand the impacts of the modernisation movement. The analytical method of Space Syntax is used to illustrate how the spatial quality of historic Sahibabad Meydan has been changed. It is revealed that the modern streets have become powerful urban elements that affect the performance of Sahibabad Meydan. Two hypotheses are considered for the future of the renovation project. Daraie Street plays a significant role in this sense as it makes a considerable impact on the visibility, accessibility, and centrality of Sahibabad Meydan. The correlation of Visual Integration and Clustering Coefficient measures reveals that the meydan will be a successful public space only if Daraie Street is closed. The present study underlines the significance of urban morphological analyses in the changing historic context. Providing the opportunity for a comparative study, Space Syntax contributes to the prediction of the future performance of an urban project.
Keywords: Historic context; meydan; space syntax; traditional Iranian cities; urban morphology